APLIKASI SELF CARE DALAM PENINGKATAN KUALITAS PERAWATAN DAN PENGELOLAAN KLIEN DIABETES MELLITUS TIPE 2 - Andi Eka Pranata; Rizki Eko Prasetyo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: Diabetes Mellitus (DM) is a chronic disease (CD) in Indonesia that contributes to high mortality. This disease poses a limitation to self-care. Good self-care prevents complications and improves the quality of life. Self-care application (SCA) is a way to increase understanding of Type 2 Diabetes Mellitus (T2DM) clients and their families to improve the quality of care and good management of T2DM clients. Objective: To determine the effect of SCA on improving the quality of care and management of T2DM clients which include blood sugar levels, nutrition management, activity/ exercise management, self aesthetics, and personal hygiene. Methods: A quasi-experimental design with a non-equivalent control group design. The population of this study was patients with type 2 diabetes with a total sample size of 50 patients with type 2 diabetes who were evenly divided into 2 research groups. The sampling method used was proportional sampling. The interventions are in the form of SCA with training and mentoring patterns of T2DM clients and their families. Data analysis using independent t-test. Result: The application of self-care had no significant impact on blood sugar stability (p 0.540), was able to improve the quality of nutritional management (p 0.018), improve activity/ exercise management (p 0.000), improve self-esthetic behavior (p 0.000), and increase personal hygiene behavior (p 0.000). Conclusion: Improving the quality of care and management of T2DM due to SCA is directly related to the understanding and awareness of T2DM clients.